A multi-dimensional omics framework identifies GPR35 as a driver of M2 macrophage activation and poor prognosis in colorectal cancer - Guan, Shen; Zhu, Liangchen; Tian, Yue; Chen, Hong; Jiang, Yiqing; Huang, Chenshen; Shi, Yuanying; Lin, Dajia (Frontiers in Immunology, 2026)
IntroductionColorectal cancer (CRC) remains a leading cause of global cancer mortality, with therapeutic outcomes heavily reliant on the tumor microenvironment (TME). While immunotherapy has revolutionized treatment for distinct subsets, the mechanisms driving immune evasion in the majority of patients remain elusive.MethodsIn this study, we constructed a comprehensive single-cell atlas of the CRC TME by integrating multi-cohort scRNA-seq data.ResultsThrough non-negative matrix factorization (NMF), we identified nine intratumoral heterogeneity meta-programs (MPs), among which MP8 was robustly linked to M2 macrophage activation. High-dimensional WGCNA further pinpointed GPR35 as a master regulator within the MP8-associated gene network. Clinical analysis across four independent cohorts validated GPR35 as a significant predictor of poor prognosis. Functionally, GPR35 knockdown in vitro markedly impaired CRC cell proliferation, migration, and invasion. Mechanistically, high GPR35 expression orchestrated an immune-excluded microenvironment characterized by diminished cytotoxic T cell and NK cell recruitment, yet paradoxically elevated immune checkpoint expression. Furthermore, GPR35 expression was negatively correlated with eight established immunotherapy response signatures and associated with aggressive mutational landscapes.DiscussionCollectively, our findings identify GPR35 as a novel cancer cell-intrinsic driver of immune evasion and immunotherapy resistance, positioning it as a promising therapeutic target to sensitize "cold" CRC tumors to immune checkpoint blockade.